Mycobacterial virulence: impact on immunogenicity and vaccine research [version 1; peer review: 4 approved] - Vera M. Kroesen; Jan Madacki; Wafa Frigui; Fadel Sayes; Roland Brosch (F1000Research, 2019)
The borderline between virulence and efficacy in live attenuated vaccine strains is often blurred and this is also the case for the Bacillus Calmette–Guérin (BCG), the only currently licensed anti-tuberculosis vaccine used on a large, global scale, which was obtained almost 100 years ago. While BCG is more than 99% identical at the genome level to Mycobacterium tuberculosis, the causative pathogen of human tuberculosis, some important differences in virulence factors cause naturally irreversible attenuation and safety of this vaccine in the immunocompetent host. Some of these virulence factors are involved in persistence capacities of the vaccine strains and also represent strong immunogens, responsible for inducing different host signaling pathways, which have to be taken into consideration for the development of revised and new vaccine strains. Here we discuss a number of selected mycobacterial features in relation to their biological functions and potential impact on virulence and vaccine efficacy.